De fraile a arzobispo. El novohispano Antonio de Monroy e Híjar (1634-1715) - Álvarez Sánchez, Adriana (El Colegio de México, A.C., 2020)
The Dominican friar Antonio de Monroy was the only priest from New Spain to become the head of his order and an archbishop in metropolitan Spain, in the archdiocese of Santiago de Compostela. This article’s goal is to analyze the works that have been published on this figure and to ask new questions based on an exhaustive review of the documents regarding his work in Europe, in the context of the geographical mobility of crown ministers, in order to contribute to the development of a biography that incorporates all facets of his life: student, friar, politician and patron of a variety of works. This article makes use of a variety of documentary sources in order to study the social history of crown ministers, who were shaped by university and convent studies; came from rich, prestigious families that were well connected, both politically and socially, in many parts of the empire; and were willing to move great distances, sometimes to another continent, in order to serve the king. The study of the career of one individual, such as Monroy, allows us to understand the international political context of both modern Europe and New Spain. It is necessary to understand the organization of the state, its functioning and its reach throughout the territories of the Spanish Crown. The search for documentation on this figure and his context has led the author to consult archives and institutional libraries in Galicia, Madrid, Simancas and Valladolid.